EPIGLOTTIS MICROFLORA OF PATIENT WITH ATTARHAL AND NECROTIC EPIGLOTTITIS - Popov, N.N.; Savchenko, A.V.; Visekancev, L.P. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Microbiological research of 100 patients with acute epiglottitis has shown that epiglottis microbial flora represented by pathogenic and opportunistic bacteria which referred to different sippes as well as to Candida fungi. Microflora of patients with necrotic epiglottitis was represented by mycobacterium association more often than in patients with catarrhal epiglottitis. Also microflora of patients with necrotic epiglottitis was represented by association of microorganisms including three or more species. Rate of microorganisms species is incompa-rably higher in patients with necrotic epiglottitis than in patients with catarrhal epiglottitis.